Possible Predictors of Involuntary Weight Loss in Patients with Alzheimer's Disease. - Massimo Venturelli; Emiliano Cè; Eloisa Limonta; Ettore Muti; Renato Scarsini; Anna Brasioli; Federico Schena; Fabio Esposito (PLoS ONE, 2016)
Loss in body mass (∆BM) is a common feature in patients with Alzheimer's disease (AD). However, the etiology of this phenomenon is unclear. The aim of this cohort study was to observe possible ∆BM in AD patients following a standard institutionalized diet. Secondary objective was to identify possible predictors of ∆BM. To this end, 85 AD patients (age: 76±4 yrs; stature: 165±3 cm; BM: 61.6±7.4 kg; mean±standard deviation) and 86 controls (CTRL; age: 78±5 yrs; stature: 166±4 cm; BM: 61.7±6.4 kg) were followed during one year of standard institutionalized diet (~1800 kcal/24h). BM, daily energy expenditure, albuminemia, number of medications taken, and cortisolism, were recorded PRE and POST the observation period. Potential predictors of ∆BM in women (W) and men (M) with AD were calculated with a forward stepwise regression model. After one year of standard institutionalized diet, BM decreased significantly in AD (-2.5 kg; p < 0.01), while in CTRL remained unchanged (-0.4 kg; p = 0.8). AD patients and CTRL exhibited similar levels of daily energy expenditure (~1625 kcal/24h). The combination of three factors, number of medications taken, albuminemia, and cortisolism, predicted ∆BM in W with AD. At contrary, the best predictor of ∆BM in M with AD was the cortisolism. Despite a controlled energy intake and similar energy expenditure, both W and M with AD suffered of ∆BM. Therefore, controlled diet did not prevent this phenomenon. The assessments of these variables may predict W and M with AD at risk of weight loss.